Politics and space in the Cairo peri-urban fringe - Awad, H (2018)
The subject of this study is local politics in Cairo’s peri-urban fringe in the Mubarak era (1981-2011). It aims to propose a new theoretical model for understanding the social dynamics at a local level that have led to a specific form of socio-political mobilization, in which social space has been central. Each chapter in this study is based on the premise that Cairo’s peri-urban fringe during the Mubarak era witnessed the rise of a dominant cognitive structure that has been responsible for shaping most of the collective political practices of local social agents. This cognitive structure has placed the representation of social space at the foreground of political representation. I call this cognitive structure ‘neighbourhoodism’. Through neighbourhoodism, social agents have been able to translate their social, cultural and symbolic capitals into political capital, thereby qualifying themselves to be locally recognized as political representatives. As this study will show, nearly all social agents in Cairo’s peri-urban fringe who sought to play a role in local politics were involved in politicizing their social spaces, at least at one stage in their political life. Those agents were from different ideological and cultural backgrounds. They encompassed actors from the local NDP, Islamists and other local figures. However, the constructing of neighbourhoodism did not happen overnight. It was an outcome of sustained social practices, individual and collective, formal and informal, which eventually resulted in an intense competition over the representation of social spaces. Although neighbourhoodism first emerged in the late 1970s, it came to dominate the political field from the late 1980s. Local communities in Cairo’s peri-urban fringe experienced an intense struggle between social agencies, who tried to protect their positions and acquire recognition by developing strategies that involved symbolic violence. Neighbourhoodism has pervaded most social groups and has led to differing cultural and ideological outcomes. Firstly, it has provided the autocratic regime with new means of control, enabling it to make clientelism more efficient and rational. Secondly, it has created a basis for the rise of new movements, most importantly the Islamic movement, by allowing it to cultivate allies from different sectors of society. Furthermore, it has motivated local groups to produce new strategies, such as clannism, in order to consolidate their position in the battle for recognition. Moreover, it gave local groups sufficient grounds to confront the state in times of conflict. The contribution of this work is to intellectually capture a social medium where the interaction between the macro and the micro can be examined to show how the local and the national/ global interact to produce localized politics, or how the local is localizing the national and vice versa.